Premature Rupture of Membrane Outcome Determinants in Reproductive Age Women - Zakirah, Sarah Chairani; Eyanoer, Putri Chairani; Azali, Chairul Nurdin; Wiweko, Budi (Journal of Maternal and Child Health, 2020)
Background: